Blockade of 5-Hydroxytryptamine 2A Receptor Attenuates Precipitation of Naloxone-Induced Withdrawal Symptoms in Opioid-Exposed Mice - Li, Bing; Jiang, Junyu; Zhou, Li; Tao, Xinrong; Sun, Qixian; Liu, Jiaxin; Liu, Yang; Pang, Gang (Frontiers in Behavioral Neuroscience, 2022)
Heroin dependency has become a global problem and has caused significant clinical and socioeconomic burdens along with devastating medical consequences. Chronic drug exposure alters the expression and functional activity of 5-hydroxytryptamine (serotonin) 2A receptors (5-HT2ARs) in the brain. Furthermore, pharmacological blockade of 5-HT2ARs reduces cue-induced cocaine craving behaviors. In this study, we explored the influence of 5-HT2ARs on heroin-withdrawal behaviors in mice. Black C57BL/6J mice were given gradually increasing (10–50 mg/kg over 4.5 days) doses of heroin to induce heroin dependency, after which naloxone was given to precipitate withdrawal symptoms. MDL100907, a selective and potent 5-HT2AR antagonist, attenuated naloxone-precipitated withdrawal symptoms in these mice. In addition, 5-HT2AR protein levels increased significantly in the medial prefrontal cortex (mPFC), while phosphorylation of extracellular signal-regulated kinase (p-ERK) decreased in the mPFC after heroin exposure. In conclusion, these results suggest that 5-HT2ARs might be involved in the development of opioid dependency and that pharmacological blocking of 5-HT2ARs might be a new therapeutic strategy for heroin dependency.